Immunohistochemical Expression of Serpin Peptidase Inhibitor B2 and Carboxypeptidase A4 in Uterine Cervical Lesions [200]. (May 2015) - Sasa, Hidenori; Suzuki, Ayako; Sei, Kiguna; Shimazaki, Hideyuki; Sugita, Michio; Furuya, Kenichi
Abstract : OBJECTIVE: Serpin peptidase inhibitor B2 is involved in the invasion and metastasis of cancer. Carboxypeptidase A4 may have a correlation with the grade of prostate cancer. We examined the immunohistochemical expression of serpin peptidase inhibitor B2 and carboxypeptidase A4 in uterine cervical lesions. MATERIALS AND METHODS: Specimens from 25 patients with uterine cervical intraepithelial neoplasia (CIN) or uterine cervical invasive carcinoma were immunohistochemically evaluated for the expression of the two markers, serpin peptidase inhibitor B2 and carboxypeptidase A4. Of the patients from whom uterine cervical cells and biopsy tissue specimens were obtained, eight had normal tissues (32%), two had CIN1 lesions (40%), eight had CIN2 lesions (32%), five had CIN3 lesions (20%), and two had cervical invasive carcinoma (8%). Immunohistochemistry staining intensity was quantitatively scored from 0 to 2+. This study was approved by the institutional review board. RESULT: The positive expression rates of serpin peptidase inhibitor B2 and carboxypeptidase A4 were 75% and 20% in the uterine cervical cells and 63% and 0% in the biopsy tissue specimens, respectively. The expression of serpin peptidase inhibitor B2 seemed to have a positive correlation with the progression of lesions, but the expression of carboxypeptidase A4 in the only dysplastic cells revealed positive. The expression of serpin peptidase inhibitor B2 was positive, but that of carboxypeptidase A4 was negative in cases of cervical invasive carcinoma. CONCLUSION: Serpin peptidase inhibitor B2 might be useful as a marker for uterine cervical lesions because it was expressed according to the grade of the CIN and cervical invasive carcinoma specimens. Carboxypeptidase A4 could be potential immunohistochemical markers for uterine cervical lesions because of positive expression in the dysplastic cells.